Field Assessment and Specification Review for Roller-Integrated Compaction Monitoring Technologies - David J. White; Pavana K. R. Vennapusa; Heath H. Gieselman (Advances in Civil Engineering)
Roller-integrated compaction monitoring (RICM) technologies provide virtually 100-percent coverage of compacted areas with real-time display of the compaction measurement values. Although a few countries have developed quality control (QC) and quality assurance (QA) specifications, broader implementation of these technologies into earthwork construction operations still requires a thorough understanding of relationships between RICM values and traditional in situ point test measurements. The purpose of this paper is to provide: (a) an overview of two technologies, namely, compaction meter value (CMV) and machine drive power (MDP); (b) a comprehensive review of field assessment studies, (c) an overview of factors influencing statistical correlations, (d) modeling for visualization and characterization of spatial nonuniformity; and (e) a brief review of the current specifications.